The Role of Infiltrated T Lymphocyte in Oral Squamous Cell Carcinoma: Insights into Clinicopathological Characteristics and Prognosis - Liao W; Lu J; Xu Y; Yang C; Chen H; Cai S; Liu L; Chen S (Dove Medical Press, 2024)
Wei Liao,1,2,* Jiaxuan Lu,3,* Yuyuan Xu,4,* Chulin Yang,1,5 Hongjie Chen,4 Shaohang Cai,4 Lili Liu,1,6 Shuwei Chen1,5 1State Key Laboratory of Oncology in South China, Guangdong Provincial Clinical Research Center for Cancer, Collaborative Innovation Center for Cancer Medicine, Guangzhou, People's Republic of China; 2Department of Intensive Care Unit, Sun Yat-sen University Cancer Center, Guangzhou, People's Republic of China; 3Hospital of Stomatology, Guanghua School of Stomatology, Guangdong Provincial Key Laboratory of Stomatology, Sun Yat-sen University, Guangzhou, Guangdong, People's Republic of China; 4Department of Infectious Diseases, Nanfang Hospital, Southern Medical University, Guangzhou, People's Republic of China; 5Department of Head and Neck Surgery, Sun Yat-sen University Cancer Center, Guangzhou, People's Republic of China; 6Department of Pathology, Sun Yat-sen University Cancer Center, Guangzhou, People's Republic of China*These authors contributed equally to this workCorrespondence: Shaohang Cai, Department of Infectious Diseases, Nanfang Hospital, Southern Medical University, Guangzhou, 510515, People's Republic of China, Email shaohangcai@foxmail.com Shuwei Chen, Department of Head and Neck Surgery, Sun Yat-sen University Cancer Center, Dongfeng East Road, Guangzhou, 510060, People's Republic of China, Email chenshuw@sysucc.org.cnBackground: To compare and analyze the presence of CD4+ and CD8 + lymphocyte infiltrates in Oral squamous cell carcinoma (OSCC) tissue versus adjacent tissue and their clinical significance.Methods: We enrolled a total of 152 patients diagnosed with OSCC, all of whom had confirmed diagnoses through pathological reports. Clinical and demographics data were extracted from medical records. Tissue microarrays were constructed and immunohistochemical staining for CD4 and CD8 was performed.Findings: The average number of infiltrating CD4+ T cells in OSCC tumor tissue was 1026.22± 1163.36 cells/mm2, which did not significantly differ from the count in adjacent tissue, which was 1163.36± 1013.23 cells/mm2. However, the number of CD8+ T cell infiltration in tumor tissue was significantly higher than in adjacent tissue (655.25± 705.70 vs 504.56± 659.26 cells/mm2, p = 0.026). We observed that, among patients who consumed alcohol, the CD4+ T cell infiltration in tumor tissue being significantly lower than that in adjacent tissue (P=0.036). Moreover, the CD8+ T cell infiltration in cancer tissue was significantly higher than in adjacent tissue for T1-2 patients (p=0.005). Patients with higher CD8+ T cell in tumor tissue exhibited significantly improved overall survival (p = 0.043). Multivariate analyses revealed that alcohol consumption had a significant impact on the number of CD4+T lymphocytes in tumor tissue (OR = 0.403, P = 0.033) while T stage was the independent factor affecting CD8+ T lymphocyte infiltration in tumor tissue (OR = 0.459, P = 0.031).Interpretation: OSCC patients with a higher number of CD8+ T lymphocyte infiltration in tumor tissue exhibited an improved prognosis.Keywords: microenvironment, OSCC, CD8 T cells, CD4 T cells, prognosis